(3SjO GddYHIs (3gfQi cjSfLQ haf OHdheGSjI GdTQb GdChSWs - (3EfOjc, eGQJfs; (3UOjb, jGSQ eMeOs ((3GdLjRI, eUQs (3OGQ fgVI eUQs, 2023)
(3dG JMed UaMGJ gPG GdcJGH JaGUjd QMdI CMO Cge h CTgQ QLGd GdOHdheGSjI GdCeQjcjI aj dGTQb GdChSW hMH dcfgG JMed JaGUjd UfGYI GdSdGe aj efWbJfG GdYQHjI GdESQGFjdjI GdJj JWhQJ HYO MQH (B6 (3GcJhHQ (B1943 (3, dbO eQ GdYGde GdYQHj HChbJG YUjHI hbGSjI HYO gRjeI (B5(3jhfjh (B1967 (3, Mjf JLGgdJ GdOhQ GdZQHjI eWGdH eUQ GdYGOdI HEYGOI GSQGFjd GdCQGVj GdJj GMJdJgG ceG YGedJ Gdbhhi GdYXei eUQ Ydi CfgG LKI gGeeOI , ef gfG jCJj CgejI GdcJGH GSJfGOG Ydi hKGFb CeQjcI hGSQGFjdjI , cja bdH GdQFjS GdSGOGJ MSGHGJ GdZQH a MQH (B6 (3CcJhQ (B1973 (3Ke Gced HYOgG eYQcI UfGYI GdS(B.(3dGes
(3GdfU eJQLe ef GddZI GdEfLdjRjI Edi GddZI GdYQHjIs
Keywords: (3gfQi cjSfLQ,s -- [1923-2023] -- (3JQGLes; (3GSQGFjds -- (3YdGbGJ NGQLjIs -- (3eUQs; (3eUQs -- (3JGQjNs -- (3CfhQ GdSGOGJ (B1970-1981s; (3GdhdGjGJ GdeJMOI GdCeQjcjIs -- (3YdGbGJ NGQLjIs; (3GJaGbjI cGeH OjajOs; (3GdOHdheGSjIs; (3GdOHdheGSjhf GdCeQjcjhfs; (3GdSdGe GdYGdeis; (3eUQs -- (3YdGbGJ NGQLjIs -- (3ESQGFjds